2019
DOI: 10.1039/c9ra07988b
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds from the seeds of Amomum tsaoko Crevost et Lemaire, a Chinese spice as inhibitors of sphingosine kinases, SPHK1/2

Abstract: New bioactive compounds were identified from the seeds of Amomum tsaoko Crevost et Lemaire, a Chinese spice as inhibitors of sphingosine kinases, SPHK1/2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…Schischk. Apiaceae root Hamaduol, Ledebouriellol, Divaricatol, Cimifugin, Anomalin, Scopoletin, Marmesin, Isofraxidin, Fraxidin, Divaricoumarin A-B-C, Kreiner et al (2017) Scutellaria baicalensis Baikal skullcap or Chinese skullcap Lamiaceae Dried root Baicalein, Wogonin, neobaicalein, and skullcapflavone Bonham et al (2005) Lanxangia tsaoko (Syn: Amomum tsao-ko) cao guo Zingiberaceae Ripe fruit and leaves cineole Lee et al (2019) …”
Section: Medicinal Plants For Viral Respiratory Infections (Vri)mentioning
confidence: 99%
“…Schischk. Apiaceae root Hamaduol, Ledebouriellol, Divaricatol, Cimifugin, Anomalin, Scopoletin, Marmesin, Isofraxidin, Fraxidin, Divaricoumarin A-B-C, Kreiner et al (2017) Scutellaria baicalensis Baikal skullcap or Chinese skullcap Lamiaceae Dried root Baicalein, Wogonin, neobaicalein, and skullcapflavone Bonham et al (2005) Lanxangia tsaoko (Syn: Amomum tsao-ko) cao guo Zingiberaceae Ripe fruit and leaves cineole Lee et al (2019) …”
Section: Medicinal Plants For Viral Respiratory Infections (Vri)mentioning
confidence: 99%
“…For a long time in history, it has been used for the interior obstruction of cold-dampness and distending pain in the epigastrium and abdomen, stuffiness and fullness, vomiting, malaria with cold and fever, and pestilence fever [5]. In recent years, A. tsaoko have been proved having anti-inflammatory effect against insects, antitumor effect in liver cancer cells, anti-angiogenesis efficacy in ovarian cancer, and inhibited sphingosine kinases 1 and 2 (SPHK1/2) [6,7]. The essential oil is one of the major active products of the black cardamom, mainly consisting of monoterpene hydrocarbons and oxygenated monoterpenes [8].…”
Section: Introductionmentioning
confidence: 99%
“…Chemical processing of the extract led to the isolation and identification of various compounds, including phenolics, fatty acids, terpenoids, and aliphatic alcohols. Two compounds exhibited inhibitory action by binding to the substrate-binding pocket of both the isoforms of SphK [ 237 ]. Lee et al [ 174 ] showed the anticancer effects of pristimerin, a triterpenoid quinone methide, that inhibits the HIF-1α accumulation via the inactivation SphK1 signaling cascade in a hypoxic prostate cancer cell line (PC-3).…”
Section: Inhibitors Of Sphkmentioning
confidence: 99%